Chemical Cutting of Perovskite Nanowires into Single‐Photon Emissive Low‐Aspect‐Ratio CsPbX3 (X=Cl, Br, I) Nanorods. (8th November 2018) - Tong, Yu; Fu, Ming; Bladt, Eva; Huang, He; Richter, Alexander F.; Wang, Kun; Müller‐Buschbaum, Peter; Bals, Sara; Tamarat, Philippe; Lounis, Brahim; Feldmann, Jochen; Polavarapu, Lakshminarayana
Abstract: Post‐synthetic shape‐transformation processes provide access to colloidal nanocrystal morphologies that are unattainable by direct synthetic routes. Herein, we report our finding about the ligand‐induced fragmentation of CsPbBr3 perovskite nanowires (NWs) into low aspect‐ratio CsPbX3 (X=Cl, Br and I) nanorods (NRs) during halide ion exchange reaction with PbX2 –ligand solution. The shape transformation of NWs‐to‐NRs resulted in an increase of photoluminescence efficiency owing to a decrease of nonradiative decay rates. Importantly, we found that the perovskite NRs exhibit single photon emission as revealed by photon antibunching measurements, while it is not detected in parent NWs. This work not only reports on the quantum light emission of low aspect ratio perovskite NRs, but also expands our current understanding of shape‐dependent optical properties of perovskite nanocrystals.